Research Trends of Public-Private Partnerships (PPPs) in Poland - Joanna Wegrzyn (Institute of Economic Research (IER), 2014)
Over the last two decades the attention given to the research on Public-private partnerships (PPPs) has been steadily increasing. A literature surveys on the research trends of PPP in English language publications suggest some emerging trends in the topics dedicated to the PPP. A similar compilation of PPP literature is not readily available on the ground on scientific research in Poland. That is why the aim of the article is to present contemporary trends that are being developed in Poland in PPP filed. Indication of possible further research in the area of PPP is also an essential issue tackled in this article.
Keywords: A10; 330; public private-partnership (PPP); systematic review; research methods